An Accessory Extensor Digitorum Longus Muscle – a Rare Variation - Saphal Lakshmi Pasupulati; Sanjit Satheesan; Piyush Saiyam; Saketh Chowdary; PK Sankaran; Kishore Sesham (Acta medica Lituanica, 2024)
During the routine dissection of lower limb in a female cadaver of age 61 years, a rare variation in the extensor digitorum longus (EDL) muscle was noticed on the both the legs. An EDL muscle with small belly dividing into two slips, which inserted on to the second and third digits on the right leg, whereas on the left leg divided into three slips, which inserted on to the second, third and fourth digits. There was also an accessory EDL muscle arising from the middle third of the medial surface of the fibula and inserted on to the fifth digit in the left foot and it inserted on to the fourth and fifth digits in the right foot. To our knowledge, such variation hasn’t been reported in literature and apprehension of such variations is important for surgeons and orthopaedicians with regards to contractures and surgical procedures concerning the anterior leg and dorsum of the foot.